Scientific Output and Thematic Development of Solar Powered Toy and Science Kit for Elementary School Students: A Comprehensive Bibliometric Review - Devita Cahyani; Andi Suhandi; Cepi Riyana; Muslim Muslim (LJPI UI Bunga Bangsa Cirebon, 2026)
Objective: This study aims to provide a comprehensive bibliometric review of research on solar-powered toys and science kits for elementary school students by mapping scientific productivity, thematic structures, and developmental trends in this emerging field. Novelty: This study offers a systematic bibliometric mapping that highlights the multidisciplinary integration of renewable energy education, STEM innovation, and hands-on learning tools specifically designed for young learners. Methods: A bibliometric analysis was conducted to examine publication trends, influential authors, leading countries, major sources, and keyword co-occurrence networks to identify dominant themes and research evolution patterns. Results: The findings reveal a steady increase in research output, reflecting growing global interest in renewable energy education for children. Three dominant themes were identified: STEM-based educational innovation, technological device development, and experimental research domains. Thematic evolution analysis indicates a shift toward experiential and hands-on learning approaches using solar-powered devices. Conclusions: This bibliometric review concludes that research on solar-powered toys and science kits for elementary school students is steadily growing, centered on STEM innovation, technological development, and experimental applications.